National Trends in Palliative Care Use among Older Adults with Cardiopulmonary and Malignant Conditions - Feder, Shelli L. (Heart Lung, 2020)
BACKGROUND: Palliative care consultation (PCC) is recommended for older adults hospitalized with cardiopulmonary conditions, but frequently is reserved for patients with malignant conditions and those with advanced age. OBJECTIVES: To compare age-adjusted PCC trends and the relationship between increasing age and PCC among older adults with cardiopulmonary and malignant conditions. METHODS: Observational analysis of patients age ≥65 years, stratified by age and cardiopulmonary (heart failure, chronic obstructive pulmonary disease) vs. malignant (lung and gastrointestinal) conditions. Age-adjusted PCC trends over time and compound annual growth rates (CAGR) were compared. RESULTS: Discharges with cardiopulmonary vs. malignant conditions were older, more likely to be female, and white. Relative to malignant conditions, discharges with cardiopulmonary conditions had lower age-adjusted PCC rates but higher CAGRS. Increasing age was associated with PCC in both groups but had a stronger effect among cardiopulmonary conditions. CONCLUSIONS: Older adults with cardiopulmonary conditions experienced lower rates of PCC, but higher rates of growth over time relative to those with malignant conditions.